2021
DOI: 10.3389/fcell.2021.729136
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage-Induced Inflammatory Microenvironment and Adult Stem Cell Response

Abstract: Adult stem cells ensure tissue homeostasis and regeneration after injury. Due to their longevity and functional requirements, throughout their life stem cells are subject to a significant amount of DNA damage. Genotoxic stress has recently been shown to trigger a cascade of cell- and non-cell autonomous inflammatory signaling pathways, leading to the release of pro-inflammatory factors and an increase in the amount of infiltrating immune cells. In this review, we discuss recent evidence of how DNA damage by af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 218 publications
(246 reference statements)
0
36
0
Order By: Relevance
“…The main feature of SCs is the ability to self-renew and differentiate. By doing so, SCs play a key role in maintaining the tissue homeostasis providing the skin (as well as the other body tissues) with differentiated mature descendant cells [ 11 , 12 , 13 , 14 ]. It has been revealed that there is a decrease in the quantity and quality of the SCs functions with age [ 15 , 16 ], which leads to depletion of the SCs pool and, thus, to a decrease in the regenerative abilities of body tissues, one of the main causes of tissue aging [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Age-related Changes In the Dermal Stem Cell Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…The main feature of SCs is the ability to self-renew and differentiate. By doing so, SCs play a key role in maintaining the tissue homeostasis providing the skin (as well as the other body tissues) with differentiated mature descendant cells [ 11 , 12 , 13 , 14 ]. It has been revealed that there is a decrease in the quantity and quality of the SCs functions with age [ 15 , 16 ], which leads to depletion of the SCs pool and, thus, to a decrease in the regenerative abilities of body tissues, one of the main causes of tissue aging [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Age-related Changes In the Dermal Stem Cell Populationmentioning
confidence: 99%
“…Disorders in the genetic apparatus of the cell occur under the influence of a number of factors, both internal and external. The internal ones include [ 14 , 18 ]: Reactive oxygen species (ROS) produced by metabolic intermediates and dysfunctional Mt; DNA replication and DNA repair errors; Glycation end products; Dysfunction and shortening of telomeres (the end regions of chromosomes that ensure stable cell replication and protect chromosomes from fusion); Inflammation of the surrounding tissue. …”
Section: Age-related Changes In the Dermal Stem Cell Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotoxic stress has recently been shown to be a trigger of an inflammatory signaling cascade which results in the release of pro-inflammatory factors and an increase in the amount of infiltrating immune cells. These events additionally contribute to ROS production and lead to the occurrence of a vicious circle of carcinogenic oxidative stress [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adult stem cells, which are found in various tissues and organs of the body, are undifferentiated cells in a differentiated tissue that can self-renew and differentiate into the specialized cells composing that tissue. These stem cells include hematopoietic stem cells, bone marrow mesenchymal stem cells, neural stem cells, muscle satellite cells, epidermal stem cells, and adipose stem cells (ASCs) ( Cinat et al, 2021 ; Menche and Farin, 2021 ). In this review, we focus on ASCs.…”
Section: Introductionmentioning
confidence: 99%